STRATEGI KOMUNIKASI PEMASARAN PUSH DAN PULL DALAM MENARIK MINAT CALON NASABAH PADA PERUSAHAAN BERJANGKA - Irawan, Shabrina Ardelia; Izaak, Wilma Cordelia (Gapenas Publisher, 2025)
The high rate of financial literacy that has not been balanced with financial inclusion in Indonesia, indicates a weak understanding of legal investment products, including futures trading. This low literacy opens a gap for the rise of investment fraud scams that harm the community. This community service activity aims to increase public literacy regarding the legality and mechanism of futures trading through an educational marketing strategy based on a push and pull approach. The push strategy is implemented through interactive workshop activities and personal follow-up through telemarketing. Pull strategy, implemented through the dissemination of educational content on social media. The service method uses qualitative with a descriptive qualitative approach with participatory observation and documentation. The results of the activity show that the push strategy is able to increase active involvement and form personal relationships which also increase the possibility of prospective customers becoming active customers. The pull strategy also succeeded in expanding the reach of information and forming digital public awareness of recognizing legal investments. The combination of these two strategies is effective in reaching the public both online and offline. This dual approach is not only relevant as a short-term educational solution but also has the potential to create long-term financial literacy.